2018
DOI: 10.1007/s11004-018-9744-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Computational Model of High-Order Stochastic Simulation Based on Spatial Legendre Moments

Abstract: Multiple-point simulations have been introduced over the past decade to overcome the limitations of second-order stochastic simulations in dealing with geologic complexity, curvilinear patterns, and non-Gaussianity. However, a limitation is that they sometimes fail to generate results that comply with the statistics of the available data while maintaining the consistency of high-order spatial statistics. As an alternative, high-order stochastic simulations based on spatial cumulants or spatial moments have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…be a set of orthogonal functions defined in the same space Ω. Then, a fixed number ω of those orthogonal functions can approximate f (z) (Lebedev 1965;Mustapha and Dimitrakopoulos 2010a;Minniakhmetov et al 2018;Yao et al 2018), when multiplied by the coefficients L i…”
Section: Joint Probability Density Function Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…be a set of orthogonal functions defined in the same space Ω. Then, a fixed number ω of those orthogonal functions can approximate f (z) (Lebedev 1965;Mustapha and Dimitrakopoulos 2010a;Minniakhmetov et al 2018;Yao et al 2018), when multiplied by the coefficients L i…”
Section: Joint Probability Density Function Approximationmentioning
confidence: 99%
“…Previous studies have shown resulting realizations that comply with the TI used but do not necessarily reproduce the spatial statistics inferred from the data (Osterholt and Dimitrakopoulos 2007;Goodfellow et al 2012). As an alternative, to address the above limitations, a high-order simulation (HOSIM) framework has been proposed as a natural generalization of the second-order-based random field paradigm (Dimitrakopoulos et al 2010;Dimitrakopoulos 2010a, b, 2011;Minniakhmetov and Dimitrakopoulos 2017a, b;Minniakhmetov et al 2018;Yao et al 2018). The HOSIM framework does not make any assumptions about the data distribution, and the resulting realizations reproduce the high-order spatial statistics of the data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. , ζ t,N ) corresponding to T , the EPDF f emp embedded in the SLM-RKHS is identical to the density estimator in Yao et al (2018) in the kernel form as…”
Section: Sequential Simulation Via Statistical Learning In Slm-kernelmentioning
confidence: 99%
“…Further developments of the high-order simulation paradigm include the simulation of spatially correlated variables (Minniakhmetov and Dimitrakopoulos 2017 ) and the direct simulation at the block scale (de Carvalho et al 2019 ). Most recently, Yao et al ( 2018 ) proposed a new computational model of high-order simulation as a unified empirical function, which avoids CPU-demanding computations of expansion coefficients. Furthermore, a kernel function can be derived from this model and will be used in the present work.…”
Section: Introductionmentioning
confidence: 99%